SENTIMENT ANALYSIS ON OAKWOOD RESIDENCE CIKARANG HOTEL REVIEWS ON TRIPADVISOR WEBSITE USING K-NEAREST NEIGHBOR ALGORITHM - Rizki Nurul Nugraha; Eviana Tarigan; Yuni Trisnawati (Sekolah Tinggi Pariwisata Mataram, 2022)
Tripadvisor is used not only as a platform to find and book hotels but also as a comparison material before buying, reviews written for a hotel will greatly influence the decisions of potential guests. One of the hotels that received the majority of Excellent ratings is Oakwood Residence Cikarang. This research has several stages, the first is called the Preprocessing stage. The second stage is to use the TF-IDF method, namely to do word weighting, the last stage is to classify the data using the K-Nearest Neighbor method. The test results related to sentiment analysis at Oakwood Residence Cikarang with the K-NN algorithm get an average accuracy of k = 3 of 90%.